Contact size, frequency and cyclic normal force effects on Ti–6Al–4V fretting wear processes: An approach combining friction power and contact oxygenation. (September 2017) - Fouvry, S.; Arnaud, P.; Mignot, A.; Neubauer, P.
Abstract: We present fretting wear analysis of a dry Ti-6Al-4V cylinder/plane contact, investigating sliding frequency, contact size, and cyclic normal force effects. The investigation showed that easy contact oxygenation promoted by low contact pressure, low frequency, small contact size and varying normal force favored a U-shape fretting scar morphology and high abrasive wear rates. By contrast, increasing contact pressure, frequency and contact size by reducing the contact oxygenation in the center of the contact promoted adhesive metal/metal interactions, transfers and TTS structures. This induced a W-shape fretting scar and lower wear rates. XPS analyses confirmed this description, highlighting Ti-nitriding processes in the under-oxygenated Ti transfers. A friction energy power density approach is introduced to predict wear rate and the U-to-W shape transition. Graphical abstract: Highlights: Abrasive "U-shape" versus adhesive "W-shape" fretting wear processes. "U-shape"/"W-shape" transition depends on friction power density and contact size. Ti-6Al-4V fretting wear rate is a power law function of friction power density. Ti-6Al-4V fretting wear process is controlled by the contact oxygenation condition.